Ketidakpuasan dalam Hubungan Biologis menjadi Alasan Poligami di Kabupaten Purbalingga: Studi Analisis Putusan Perkara No.2126/Pdt.G/2021/PA.Pbg - Marwati, Lusi; Mutakin , Ali; Isyanto, Nur (Tasyri' : Journal of Islamic Law, 2024)
Licensing for polygamy is the granting of rights by the Religious Courts to someone to marry more than one wife. As for efforts to implement a polygamy permit, it must comply with the applicable terms and conditions, as stated in Article 4 paragraph (2) and Article 5 paragraph (1). This article aims to analyze the provisions of the decision No. 2126/Pdt.G/2021/PA. Pbg, regarding polygamy licensing. The type of research used is a normative legal research model. The primary data source used is a copy of the decision No. 2126/Pdt.G/2021/PA. Pbg, while secondary data is in the form of books, journals, and interviews. The data analysis technique uses descriptive analysis, where the data obtained is described and then analyzed. The findings of this article are several considerations that are used as a reference for judges in making decisions no. 2126/Pdt.G/2021/PA. Pbg, namely: 1) Based on Article 4 paragraph (2), Article 5 paragraph (1), and law number 1 of 1974. 2) Based on written and oral evidence from the respondent and the statements of the two witnesses. 3) Based on benefit considerations